The Discovery of Potent Nonstructural Protein 5A (NS5A) Inhibitors with a Unique Resistance Profile—Part 1. Issue 7 (11th April 2014) - Tran, Thien Duc; Wakenhut, Florian; Pickford, Chris; Shaw, Stephen; Westby, Mike; Smith‐Burchnell, Caroline; Watson, Lesa; Paradowski, Michael; Milbank, Jared; Brimage, Rebecca A.; Halstead, Rebecca; Glen, Rebecca; et al.
Abstract Nonstructural protein 5A (NS5A) represents a novel target for the treatment of hepatitis C virus (HCV). Daclatasvir, recently reported by Bristol–Myers–Squibb, is a potent NS5A inhibitor currently under investigation in phase 3 clinical trials. While the performance of daclatasvir has been impressive, the emergence of resistance could prove problematic and as such, improved analogues are being sought. By varying the biphenyl‐imidazole unit of daclatasvir, novel inhibitors of HCV NS5A were identified with an improved resistance profile against mutant strains of the virus while retaining the picomolar potency of daclatasvir. One compound in particular, methyl ((S)‐1‐((S)‐2‐(4‐(4‐(6‐(2‐((S)‐1‐((methoxycarbonyl)‐L‐valyl)pyrrolidin‐2‐yl)‐1H‐imidazol‐5‐yl)quinoxalin‐2‐yl)phenyl)‐1H‐imidazol‐2‐yl)pyrrolidin‐1‐yl)‐3‐methyl‐1‐oxobutan‐2‐yl)carbamate (17), exhibited very promising activity and showed good absorption and a long predicted human pharmacokinetic half‐life. This compound represents a promising lead that warrants further evaluation.